1977
DOI: 10.1136/thx.32.4.486
|View full text |Cite
|
Sign up to set email alerts
|

Lung function of healthy boys and girls in Jamaica in relation to ethnic composition, test exercise performance, and habitual physical activity

Abstract: . (1977). Thorax, 32,[486][487][488][489][490][491][492][493][494][495][496]. Lung function of healthy boys and girls in Jamaica in relation to ethnic composition, test exercise performance, and habitual physical activity. The relationships of forced expiratory volume and forced vital capacity on height, age, sex, area of residence, and ethnic composition were assessed in 622 children in Jamaica. Rural children in hill-farming communities were judged to have a higher habitual physical activity than urban child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
2
2

Year Published

1991
1991
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 19 publications
3
18
2
2
Order By: Relevance
“…Predictive studies for North American and European populations found lower values in minorities such as blacks or Hispanics, but their lower socioeconomic and nutritional status are probably important confounding factors (4,7,21). Studies with immigrants suggest that intermarriage can induce LV values which are intermediate between the parents (32,35). Our results are probably influenced by the multiracial profile of the urban Brazilian population, and therefore one would expect intermediate values, for example between Caucasians and blacks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Predictive studies for North American and European populations found lower values in minorities such as blacks or Hispanics, but their lower socioeconomic and nutritional status are probably important confounding factors (4,7,21). Studies with immigrants suggest that intermarriage can induce LV values which are intermediate between the parents (32,35). Our results are probably influenced by the multiracial profile of the urban Brazilian population, and therefore one would expect intermediate values, for example between Caucasians and blacks.…”
Section: Discussionmentioning
confidence: 99%
“…There is a considerable amount of data concerning the effects of race and ethnicity in LV and pulmonary function testing (32)(33)(34)(35), but little is known about the precise underlying physiological mechanisms. Predictive studies for North American and European populations found lower values in minorities such as blacks or Hispanics, but their lower socioeconomic and nutritional status are probably important confounding factors (4,7,21).…”
Section: Discussionmentioning
confidence: 99%
“…It is a well known fact that pulmonary function parameters are influenced by race age, sex, height, weight and other unknown variables having a wide range of normal values [13,14,15,16]. The large metabolic demand of strenuous exercise requires an efficient oxygen transport system from the atmosphere to the active tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Los estudios realizados en diversas poblaciones han mostrado diferencias importantes en los parámetros de la espirometría, según las diferentes etnias (1)(2)(3)(4)(5)(6). Además, se ha encontrado que la ubicación geográfica, la nutrición y la exposición ambiental influyen sobre la función pulmonar (4,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21).…”
unclassified